Dual-responsive nanosystem based on TGF-β blockade and immunogenic chemotherapy for effective chemoimmunotherapy - Huang, Xiaoxian; Han, Lingfei; Wang, Ruyi; Zhu, Wanfang; Zhang, Ning; Qu, Wei; Liu, Wenyuan; Liu, Fulei; Feng, Feng; Xue, Jingwei (Drug delivery, 2022)
The antitumor immune response induced by chemotherapy has attracted considerable attention. However, the immunosuppressive tumor microenvironment hinders the immune activation effect of cancer chemotherapy. TGF-β plays a key role in driving tumor immunosuppression and can prevent effective antitumor immune response through multiple roles. In this study, a dual-responsive prodrug micelle (PAOL) is designed to co-deliver LY2109761 (a TGF-β receptor I/II inhibitor) and oxaliplatin (OXA, a conventional chemotherapy) to remodel tumor microenvironment and trigger immunogenic cell death (ICD) to induce antitumor immunity response. Under hypoxia tumor environment, the polyethylene glycol shell of the micelle cleavages, along with the release of LY2109761 and OXA prodrug. Cytotoxic effect of OXA is then activated by glutathione-mediated reduction in tumor cells and the activated OXA significantly enhances tumor immunogenicity and promotes intratumoral accumulation of cytotoxic T lymphocytes. Meanwhile, TGF-β blockade through LY2109761 reprograms tumor microenvironment by correcting the immunosuppressive state and regulating tumor extracellular matrix, which further maintaining OXA induced immune response. Therefore, due to the capability of boosting tumor-specific antitumor immunity, the bifunctional micelle presents markedly synergistic antitumor efficacies and provides a potent therapeutic strategy for chemoimmunotherapy of solid tumors.